Analisis Penerimaan Aplikasi SIDERING dari Perspektif Theory of Planned Behavior (TPB) Pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu (DPMPTSP) Kabupaten Magelang - Orbi Anjani, Galuh; Nugraha, Joko Tri; Fadhlurrahman; Iriani Sinuraya, Suci (Sawala : Jurnal Administrasi Negara, 2024)
The low adoption rate and lack of public knowledge regarding the SIDERING application in Magelang Regency are caused by various factors, such as public perception of the usefulness and ease of use of the application, as well as other factors that influence user intentions and behavior in adopting the SIDERING application. The study aims to analyze the level of acceptance of the SIDERING application using the Theory of Planned Behavior (TPB) model, and using five variables. The method used is quantitative by distributing questionnaires to respondents who use the SIDERING application. The data is in accordance with the instruments in the TPB. Data processing of the study used SPSS Statistics Version 29 to process, measure, and analyze the relationship between constructs. The results of the study showed that the research hypothesis was entirely accepted. The Theory of Planned Behavior (TPB) approach predicts relevantly where behavioral intentions to use the SIDERING application are clearly influenced by attitudes, subjective norms, perceived behavioral control, and interests. The level of acceptance of the use of the SIDERING application at the DPMPTSP Magelang Regency is quite acceptable and has been used well by SIDERING application users